The Use of Ovitrap and the Female Aedes sp. Density in the Tamansari Village of Bandung City - Trusda, Siti Annisa Devi; Astuti, Ratna Dewi Indi; Tresnasari, Cice (Universitas Islam Bandung, 2023)
Dengue hemorrhagic fever (DHF) incidence in Indonesia, which become one of the mortality causes, is relatively high. Therefore, the government launched the mosquito nest eradication (MNE) movement with an indicator of the larva-free rate to reduce the incidence of DHF. Another effort in vector control is using ovitrap to break the life chain of dengue vectors. This study aimed to determine the effect of using ovitrap on the female Aedes sp. density in the Tamansari village area of Bandung city. This quantitative experimental study was conducted on 60 houses in two neighborhood associations in the Tamansari village area. Both community groups were assessed for ovitrap index and the number of eggs trapped on ovitrap filter paper before and after treatment. The treatment group consisting of 30 houses was given one ovitrap inside and one ovitrap outside the house for four weeks. Ovitrap is changed every five days. The second group is the control community. The data obtained were analyzed using the Wilcoxon and chi-square tests with a degree of confidence of 0.05. In this study, the ovitrap index of this area was found between 0.67–0.80, which indicates that this area is at high risk of DHF transmission. Statistical tests showed that the use of ovitrap did not affect female Aedes sp. density as assessed by the ovitrap index. The results showed that using ovitrap could not control the population of Aedes sp.